2023
DOI: 10.21608/menj.2023.289272
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Motivation Based Nursing Intervention on Physical Activity and Cardiac Self-Efficacy among Patients with Coronary Heart Diseases

Abstract: Coronary heart diseases are leading causes of death worldwide. Improvements in physical activity behavior and cardiac self-efficacy are useful to adopt a healthy lifestyle and to promote person-centered care in practice. Purpose: to examine the effect of motivation based nursing intervention on physical activity and cardiac self-efficacy among patients with coronary heart diseases. Design: A quasi-experimental design (study-control group) was used. Setting: The study conducted at the cardiology outpatient clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 5 publications
(6 reference statements)
0
8
0
Order By: Relevance
“… Quasi-experimental 104 patients with CAD IG (n=52) CG (n=52) Educational with posters, power points and a booklet Hospital-based This intervention can increase satisfaction scores, cardiac SE, and cardiac exercise SE, and reduce somatic health complaints and anxiety levels (p<0.001). Pre-test IG (20.99±8.8); CG (22.92±10.62) Post-test IG (78.02±10.12); CG (24.08±10.26) Iran 40 Increase self-efficacy and health literacy level Quasi-experimental 56 patients with ACS IG (n=28) CG (n=28) Family-centered self-care program with video call WhatsApp Hospital-based This intervention can increase the level of health literacy and self-efficacy (p<0.001) Pre-test IG (36.84±13.17); CG (35.22±13.30) Post 4 weeks IG (57.18±3.5); CG (34.71±10.11) Egypt 2 Improve SE Quasi-experimental 70 myocardial infarction patients IG (n=35) CG (n= 35) Educational Program with discussion, demonstration and booklet methods Hospital-based The educational program can improve self-efficacy ( p =0.001) Baseline IG (37.1±15.42); CG (35.51±12.44); FU-3 months IG (48.05±10.8); CG (35.35±12.07) Egypt 41 Increase motivation in physical activity and cardiac SE Quasi-experimental 370 patients with CHD IG (n=185) CG (n= 185) Motivation-based nursing intervention with booklet Clinic This intervention had a significant positive effect on physical activity levels (p<0.001) and cardiac SE (p=0.002) Baseline IG (19.7±7.4); CG (20.04±6.2) After 6 months IG (28.8±8.6); CG (20.9±6.6) Indonesia 29 Improve SE and quality of life Quasi-experimental 37 patients with CHD IG (n=18) CG (n= 19) Workbook in Health Education Hospital-based Workbook can improve SE ( p =0.009) Baseline IG (79.2±3.85); CG (79.7±4.24) FU-2 months IG (97.6±4.9...…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“… Quasi-experimental 104 patients with CAD IG (n=52) CG (n=52) Educational with posters, power points and a booklet Hospital-based This intervention can increase satisfaction scores, cardiac SE, and cardiac exercise SE, and reduce somatic health complaints and anxiety levels (p<0.001). Pre-test IG (20.99±8.8); CG (22.92±10.62) Post-test IG (78.02±10.12); CG (24.08±10.26) Iran 40 Increase self-efficacy and health literacy level Quasi-experimental 56 patients with ACS IG (n=28) CG (n=28) Family-centered self-care program with video call WhatsApp Hospital-based This intervention can increase the level of health literacy and self-efficacy (p<0.001) Pre-test IG (36.84±13.17); CG (35.22±13.30) Post 4 weeks IG (57.18±3.5); CG (34.71±10.11) Egypt 2 Improve SE Quasi-experimental 70 myocardial infarction patients IG (n=35) CG (n= 35) Educational Program with discussion, demonstration and booklet methods Hospital-based The educational program can improve self-efficacy ( p =0.001) Baseline IG (37.1±15.42); CG (35.51±12.44); FU-3 months IG (48.05±10.8); CG (35.35±12.07) Egypt 41 Increase motivation in physical activity and cardiac SE Quasi-experimental 370 patients with CHD IG (n=185) CG (n= 185) Motivation-based nursing intervention with booklet Clinic This intervention had a significant positive effect on physical activity levels (p<0.001) and cardiac SE (p=0.002) Baseline IG (19.7±7.4); CG (20.04±6.2) After 6 months IG (28.8±8.6); CG (20.9±6.6) Indonesia 29 Improve SE and quality of life Quasi-experimental 37 patients with CHD IG (n=18) CG (n= 19) Workbook in Health Education Hospital-based Workbook can improve SE ( p =0.009) Baseline IG (79.2±3.85); CG (79.7±4.24) FU-2 months IG (97.6±4.9...…”
Section: Resultsmentioning
confidence: 99%
“…It is found that 15 educational methods were carried out in hospitals, clinics, and patients’ homes. Table 3 shows that the most frequently used media is booklets, 2 , 28 , 39 , 41 , 42 and intervention frequency in 1–6 sessions. However, four studies did not mention the frequency of intervention delivery.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations